Employment status and epilepsy - C. Arambepola; I. Wijesekera (College of Community Physicians of Sri Lanka, 2003)
Objectives: To determine the influence of epilepsy, namely, nature of seizures, effects of anti-epileptic drugs and social stigma on the employment status of patients with epilepsy.   Methods: A hospital clinic based cross sectional study was conducted over a period of one month among 217 non schooling adult patients with epilepsy attending the Neurology clinic, NHSL. An interviewer-administered questionnaire that derived information on disease characteristics and employment status was used.   Results: Nearly 37% of the patients was currently employed. Of the unemployed, 45% were previously employed and 55% were never employed. Under-employment was not reflected among the employed patients. Although performance at work revealed a gender difference (p<0.01), absenteeism related to epilepsy did not. Age of onset, duration and stigma of epilepsy were significantly related to current employment status (p<0.01). Stigma was the only disease characteristic that was associated with poor performance at work (p<0.01) and was the commonest reason for losing jobs and for remaining unemployed, Seizure severity was associated only with absenteeism. Antiepileptic-drug effects did not associate with any variable considered (p>0.5). Although educational status was poor among the unemployed (p<0.01), it could not be associated with early age of onset of epilepsy (p>0.05).   Conclusions: More than one facet of the employment status was affected by epilepsy in the majority of patients, stigma being the major contributor.